2008
DOI: 10.1111/j.1365-2958.2008.06232.x
|View full text |Cite
|
Sign up to set email alerts
|

The essentiality and involvement of Streptococcus intermedius histone‐like DNA‐binding protein in bacterial viability and normal growth

Abstract: SummaryStreptococcus intermedius histone-like DNA-binding protein (Si-HLP) is a homodimeric protein and, conserved with Escherichia coli HU, a well-documented nucleoid-associated protein (NAP). In E. coli, HU plays important roles as both structural and regulatory factors, but it is not essential for E. coli viability. Streptococcal HLP has been found to bind host cells and induce cytokine production, but its physiological role remains poorly defined. In the present study, using gene insertion knockout and tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 75 publications
0
41
0
Order By: Relevance
“…In general, untagged GFP is difficult to image because the fluorescence signal spreads through the entire cytoplasm by fast diffusion during the image acquisition time and is overwhelmed by cellular autofluorescence (37,38). To overcome this problem, we fused sfGFP(Bs) and mKate2 (here called gfp and rfp, respectively) to the 3= end of hlpA (SPD_0997), encoding the only known nucleoid binding protein in Streptococcus (39), and stably integrated the fusions by double crossover in the pneumococcal chromosome at the hlpA locus (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…In general, untagged GFP is difficult to image because the fluorescence signal spreads through the entire cytoplasm by fast diffusion during the image acquisition time and is overwhelmed by cellular autofluorescence (37,38). To overcome this problem, we fused sfGFP(Bs) and mKate2 (here called gfp and rfp, respectively) to the 3= end of hlpA (SPD_0997), encoding the only known nucleoid binding protein in Streptococcus (39), and stably integrated the fusions by double crossover in the pneumococcal chromosome at the hlpA locus (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…S.i.-HLP was found to bind host cells and induce cytokine production. 28 It was reported that stimulation with recombinant S.i.-HLP (rS.i.-HLP) induced the secretion of IL-8, IL-1b, and tumor necrosis factor-a in human monocytic cell line THP-1. The stimulatory effect of rS.i.-HLP was cooperative by costimulation with LTA.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophoretic mobility shift assay was carried out as described by Liu et al (23). Briefly, a supercoiled plasmid, pGEMT (6 nM), was incubated with increasing amounts (60, 600, and 6,000 nM) of purified HP119 protein or bovine serum albumin (BSA) in reaction buffer (10 mM Tris [pH 8.0], and 75 mM KCl) at 25°C for 25 min.…”
Section: Methodsmentioning
confidence: 99%